Violence is not always violence. Its meaning to homeless children - Valencia González, Alejandra; Alcaraz López, Gloria Margarita (Investigación y Educación en Enfermería, 2010)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Objective. To describe and understand violence meaning for children with street living experience in the city of Medellin. Methodology. Ethnographic study performed between February 2005 and May 2008, 10 boys and 8 girls under 18 years old who accepted to participate were interviewed. Observations were made during day and night hours. From the analytical process emerged the categories of non violent aggressions and the violence that is to damage without reason. Results. Non violent aggressions in the street surge from the peer relationship as a defense mechanism this is why they are valid and legitimate, contrary to this violence is executed by people estranger to the logics of the street, seeking to cause damage; their actions are not justified and therefore are illegitimate. In the buildup that children make about violence and non violent aggressions, there is a background of survival and absence of institutions that guarantee their rights, such absence increases the feelings of suffering and pain already present for the previously experimented violence. These children go through the streets making history in adversity, creating laws and logics that allow them to survive. The laws established in the street anti law claim for inclusive, designed programs from their specific necessities so that they can part of the society as subjects with rights to be acknowledge all their human dignity. Conclusion. For homeless children violence is classified and seen as violence, in this sense they legitimate it.